1990
DOI: 10.1084/jem.171.5.1567
|View full text |Cite
|
Sign up to set email alerts
|

Gamma/delta T cell clones and natural killer cell clones mediate distinct patterns of non-major histocompatibility complex-restricted cytolysis.

Abstract: Non-MHC-restricted killer cells are cytotoxic lymphocytes that can mediate cytolysis of most tumor targets without apparent selectivity and restriction by the MHC, particularly when activated with IL-2. These effector cells include predominantly NK cells and T cells expressing the TCR-gamma/delta. We found that TCR-gamma/delta-1+, delta TSC1-, BB3+, Ti gamma A+ T cell clones mediate a characteristic cytolytic pattern of non-MHC-restricted cytolysis that is markedly different from NK clones and alpha/beta T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(83 citation statements)
references
References 35 publications
2
81
0
Order By: Relevance
“…Our data are consistent with the results of the other researchers [21]. Like NK cells, Υ δ T cells in human peripheral blood mediate the non-MHC-restricted cytolytic effect against many tumor cells.…”
Section: Discussionsupporting
confidence: 83%
“…Our data are consistent with the results of the other researchers [21]. Like NK cells, Υ δ T cells in human peripheral blood mediate the non-MHC-restricted cytolytic effect against many tumor cells.…”
Section: Discussionsupporting
confidence: 83%
“…The membrane localisation of HSP was observed directly by immunofluorescence on activated mononuclear phagocytes (Wurttenberg et al, 1991) and in the course of viral infections (La Thangue & Latchman, 1988), and indirectly by the fact that TT/6 lymphocytes recognises HSP on Daudi cells (Fish et al, 1990). In this context, HSP recognition might represent a mechanism for the role of HSP in autoimmunity and microbial infections (Kaufmann, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Esslin and Formby 7 showed that in vitro activated peripheral blood ␥␦ + T cells possess MHC non-restricted cytolytic activity towards selected human tumor cell lines when compared to similarly activated ␣␤ + T cells. Others have shown that heat shock proteins, [17][18][19] TCT.1 20 and the nonclassical human MHC antigens MICA and MICB 16 also function as ligands for ␥␦ + T cells. Cytotoxic ␥␦ + T cells have been generated against EBV-transformed B cells, 21 Burkitt lymphoma cells, 21 Daudi lymphoma cells, 22 and against autologous maturing hematopoietic cells from a patient with aplastic anemia.…”
Section: Discussionmentioning
confidence: 99%